SAT0675 SERUM CALPROTECTIN IN EARLY RHEUMATOID ARTHRITIS: ASSOCIATION WITH DISEASE ACTIVITY AND CLINICAL REMISSION. (June 2019) - Zou, Yuhan; Lahiri, Manjari; Teoh, Lay Kheng; Dharmadhikari, Bhushan; Kow, Nien Yee; Mak, Anselm; Cheung, Peter
Abstract : Background: Although remission is the goal of treatment in early rheumatoid arthritis (ERA), there is a lack of a sensitive biomarker for evaluating stringent clinical remission. Calprotectin is a potential biomarker for this purpose as it plays a critical role in synovial inflammation, cartilage destruction and bone resorption and its levels are reflective of local joint inflammation. 1, 2 Objectives: The study compares calprotectin with acute phase reactants such as erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) in discriminating stringent clinical remission from low disease activity (LDA) to moderate disease activity (MDA) in patients with ERA. Methods: A cross-sectional study was conducted on ERA patients from the Singapore Early Arthritis Cohort study. Serum calprotectin, ESR and CRP levels were measured. Receiver operating characteristics curves were used to compare the biomarkers in determining remission according to the Disease Activity Score in 28 Joints with ESR and CRP (DAS28ESR and DAS28CRP), Clinical Disease Activity Index (CDAI) and Simplified Disease Activity Index (SDAI). Results: Eighty ERA patients were included: 72.5% female, 61.3% Chinese, 66.3% seropositive, mean (S.D.) age 54.1 (12.2) and disease duration 2.3 (0.9) years. Calprotectin was significantly correlated with the DAS28ESR (rs =0.509, P -value<0.001), DAS28CRP (rs =0.486, P -value<0.001), CDAI (rs =0.487, P -value=0.021) and SDAI (rs =0.567, P -value=0.002). Calprotectin had the highest area under the curve (AUC) for discriminating remission based on the DAS28ESR (AUC=0.782, 95% CI 0.659 to 0.868), CDAI (AUC=0.753, 95% CI 0.627 to 0.855) and SDAI (AUC=0.829, 95% CI 0.693 to 0.937). A calprotectin cut-off of 98.9 ng/ml determined remission by the CDAI (sensitivity 0.82, specificity 0.53, 80.0% correctly classified) and a cut-off of 89.4 ng/ml determined remission by the SDAI (sensitivity 0.90, specificity 0.68, 87.5% correctly classified). 96.3% of patients were treated with conventional synthetic disease-modifying antirheumatic drugs (csDMARDs). Conclusion: Calprotectin is a sensitive biomarker for evaluating stringent clinical remission and can potentially be integrated into treat-to-target algorithms to guide management in ERA patients with apparently quiescent disease activity. References: [1] Bae SC, Lee YH. Calprotectin levels in rheumatoid arthritis and their correlation with disease activity: a meta-analysis. Postgrad Med 2017;129(5):531-7. [2] Kopec-Medrek M, Widuchowska M, Kucharz EJ. Calprotectin in rheumatic diseases: a review. Reumatologia 2016;54(6):306-9. Acknowledgement: This work was supported by the National University Hospital University Medicine Cluster Junior Research Award (JRA/Nov17/U002). Disclosure of Interests: Yuhan Zou: None declared, Manjari Lahiri Grant/research support from: Grant support from Pfizer. I am the site PI for the Singapore National Biologics Register which is funded by multiple pharmaceutical companies; however I do not directly receive any funds for this., Consultant for: Advisory board for Elli Lilly, Lay Kheng Teoh: None declared, Bhushan Dharmadhikari: None declared, Nien Yee Kow: None declared, Anselm Mak: None declared, Peter Cheung: None declared